2014
DOI: 10.1002/bse.1865
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Corporate Environmental Disclosure

Abstract: In this paper, we have studied the factors that influence the environmental disclosures of Italian\ud listed companies. We also aimed to verify the effects produced by the introduction of specific\ud legislation (albeit of a voluntary nature) on environmental disclosures. The analysis has the\ud advantage of including all of the informational documents produced by the company. The analysis\ud shows an (excessively) low level of disclosure of environmental information by the companies\ud examined. The econometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
0
6

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 85 publications
(145 reference statements)
8
81
0
6
Order By: Relevance
“…To avoid model misspecification, we control for additional variables that could influence the CESD practices. Following prior literature, we control for firm size (FSIZE), which is measured as the natural log of total assets (see D'Amico et al , ; Liao et al , ; Tauringana and Chithambo, ). We also control for firm profitability, measured by return on assets (ROA) (Brammer and Pavelin, ; Clarkson et al , ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid model misspecification, we control for additional variables that could influence the CESD practices. Following prior literature, we control for firm size (FSIZE), which is measured as the natural log of total assets (see D'Amico et al , ; Liao et al , ; Tauringana and Chithambo, ). We also control for firm profitability, measured by return on assets (ROA) (Brammer and Pavelin, ; Clarkson et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…We also control for firm profitability, measured by return on assets (ROA) (Brammer and Pavelin, ; Clarkson et al , ). We account for the effect of firm leverage (LEV) on disclosure practices, measured through the ratio of long‐term debt to total assets (D'Amico et al , ). In line with prior research (Tauringana and Chithambo, ), we also control for the effect of financial slack (SLACK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the variables that positively affect disclosure, international literature has generally included firm size (Adams et al [93]; D'Amico et al [94]; García-Sánchez [95]). There are various reasons for this inclusion.…”
Section: Firm Sizementioning
confidence: 99%
“…An analysis of the disclosures made by textile companies in Bangladesh [12] revealed that only 9 of the 29 companies puts any environmental information in the annual report. Also, a study of Italian listed companies indicate a low level of disclosure of environmental information [7]. It should be emphasized that there is a tendency of increasing the number of companies making environmental disclosure and improving the quality of the disclosure over time [10], [13], [19], [20].…”
Section: Literature Reviewmentioning
confidence: 99%